Contact with recovered peers: buffering disempowering service experiences and promoting personal recovery in serious mental illness. Issue 6 (November 2019) - McLeod, Bronte; Meyer, Denny; Murray, Greg; Foley, Fiona; Jones, Nev; Thomas, Neil
Abstract : Background: Mental health patients can experience involuntary treatment as disempowering and stigmatising, and contact with recovered peers is cited as important for countering stigma and fostering agency and autonomy integral to recovery. Aims: To advance understanding of the interaction between involuntary treatment and contact with recovered peers, and explore hypothesised relationships to mechanisms of self-evaluation relevant to recovery. Method: Eighty-nine adults diagnosed with serious mental illness completed items to assess involuntary treatment experience and the extent of prior contact with recovered peers, the Internalised Stigma of Mental Illness Scale, the Self-efficacy for Personal Recovery Scale, the Questionnaire about the Process of Recovery and relevant demographic and clinical scales. Results: Contact with recovered peers was found to moderate the effects of involuntary treatment on internalised stigma. Sequential conditional process models (i.e. moderated mediation) then demonstrated that conditional internalised stigma (i.e. moderated by contact with recovered peers) mediated the indirect effect of involuntary treatment on recovery-specific self-efficacy, which in turn influenced recovery. Compared with those with low contact with recovered peers, recovery scores were 3.54 points higher for those with high contact. Conclusions: Although study methods limit causative conclusions, findings are consistent with proposals that contact with recovered peers may be helpful for this patient group, and suggest this may be particularly relevant for those with involuntary treatment experience. Directions for future research, to further clarify measurement and conceptual tensions relating to the study of (dis)empowering experiences in mental health services, are discussed in detail.